Pentecostal currents and individual mobility: visiting church services in Stockholm County - Jessica Moberg (Approaching Religion, 2015)
The classification of Pentecostal currents and organizations has been widely debated within Pentecostal studies. In contemporary Sweden, the disintegration of historically important boundaries (denominational, practical and theological), as well as increased mobility between Pentecostal organizations, illustrates that the issue deserves further attention. If many of the old boundaries are being suspended, how may we distinguish between different Pentecostal varietie-s, and what role do such differences play for today’s mobile practitioners? The present article, which consists of a case study of Stockholm County, approaches the matter from a Bourdieu-influenced perspective, where differences are understood in terms of habitus. The study draws upon fieldwork in 16 congregations, carried out between 2009 and 2013, and concludes that three variations of the habitus can in fact be distinguished in the Pentecostal movement of Stockholm County; low key, grand and informal. The differences between these forms in fact impacts upon patterns of mobility among individual Pentecostalists; most prefer congregations of the same variety, even though there are examples of practitioners who visit other forms of organizations as well.